2022
DOI: 10.3389/fimmu.2022.859331
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: CCDC88A Post-Transcriptionally Regulates VEGF via miR-101 and Subsequently Regulates Hepatocellular Carcinoma

Abstract: BackgroundmiR-101 is one of the most abundantly expressed microRNA (miRNA) and exerst a critical role in hepatocellular carcinoma (HCC) by targeting to 3’ -untranslated region (UTR) of Girders of actin filaments (CCDC88A) and Vascular endothelial growth factor (VEGF) mRNA, but the underlying molecular mechanism remains to be elucidated. This study aimed to investigate the potential role of CCDC88A on malignancies and stemness by regulating VEGF via miR-101 in HCC.MethodsGene Expression Profiling Interactive An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…TEAD2 has been found to be relevant to tumor suppression by restricting proliferation and promoting apoptosis through the Hippo signaling pathway [42,43]. CCDC88A serves as a nonreceptor guanine nucleotide exchange factor which binds to and activates guanine nucleotide-binding protein G (i) alpha subunits, involved in multiple biological processes, such as cell migration and cellular immunity [44][45][46][47][48]. However, the specific role of these six genes in CLL has not been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…TEAD2 has been found to be relevant to tumor suppression by restricting proliferation and promoting apoptosis through the Hippo signaling pathway [42,43]. CCDC88A serves as a nonreceptor guanine nucleotide exchange factor which binds to and activates guanine nucleotide-binding protein G (i) alpha subunits, involved in multiple biological processes, such as cell migration and cellular immunity [44][45][46][47][48]. However, the specific role of these six genes in CLL has not been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased miR-101 promotes cancer cell proliferation by increasing the expression of numerous oncogenes. In hepatocellular carcinoma, miR-101 is proven to specifically bind to vascular endothelial growth factor (VEGF) mRNA three prime untranslated region (3′-UTR) to decrease protein levels of VEGFA (one of the main isotypes of VEGF) [ 21 ] and inhibit VEGFR2 signaling pathway thereby impair the malignant behavior of HCC cells. MiR-101 could also inhibit the proliferation of liver cancer cells by targeting zinc finger protein 217 (ZNF217), mitogen-activated protein kinases (MAPK)/extracellular signal-regulated kinase (ERK) signaling pathways, and hepatocyte growth factor (HGF)/c-MET axis [ 22 , 23 , 24 ].…”
Section: Mir-101 Regulates Cancer Growth Metastasis and Therapeutic R...mentioning
confidence: 99%
“…By using the liver cancer model, Wang et al found that overexpression of miR-101 could significantly reduce the level of VEGF, and further studies confirmed that miR-101 affected the secretion of VEGF by inhibiting the expression of junB proto-oncogene/AP-1 transcription factor subunit (JunB) [ 73 ]. MiR-101 was found to target VEGF mRNA 3′-UTR to regulate its expression in hepatocellular carcinoma [ 21 ]. Moreover, the VEGF mRNA is also identified as the target of miR-101 in cholangiocarcinoma cells.…”
Section: Mir-101 Inhibits Cancer By Remodeling the Tumor Ecosystemmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies of HCC, many miRNAs have been proven to be involved in the regulation of tumor proliferation, invasion and metastasis [ 16 , 17 , 18 ]. For example, Qiongying Hu et al [ 19 ] confirmed that miR-101 can suppress HCC progression by decreasing the expression level of VEGF. MiRNAs may become novel breakthroughs or therapeutic targets for seeking new therapeutic methods for HCC.…”
Section: Introductionmentioning
confidence: 99%